O Supremo Tribunal Federal e a demarcação da terra indígena Raposa Serra do Sol: sujeitos, ambiguidades e poderes na principal corte jurídica do país - Anabelle Santos Lages (2014)
One can consider the Supreme Federal Court as one of the most watched institutions in the country today. Its decisions are a frequent theme in the editorials and the subject of debate among ordinary citizens. There are no doubts about the immense power that it possess. But how the professional and personal education along with the external conditions imposed upon the eleven ministers affects their decision reasoning? In which way these individuals guarantee day to day respect to the multiculturalism protected by the 1988 Republic's Constitution? Using the decision reached by this institution in the judicial process regarding the delimitation of the indigenous land Serra do Sol, this research intends to understand how this elite group acted in a multi-ethnic and multi-cultural case, in a litigation with strong economic and territorial interests.